Gender is an independent risk factor for distribution pattern and lesion morphology in chronic critical limb ischemia - Ortmann, Jana; Nüesch, Eveline; Traupe, Tobias; Diehm, Nicolas; Baumgartner, Iris (Journal of vascular surgery, 2012)
The aim of this study was to determine gender differences in atherosclerotic lesion morphology and distribution pattern of patients with critical limb ischemia (CLI). In this prospective cohort study, 233 patients, including 134 men (58%) and 99 women (43%) presenting with critically ischemic limbs were consecutively enrolled. Lesions of the entire lower limb arterial tree were evaluated and grouped into iliac, femoropopliteal, and below-the-knee (BTK) arterial disease. To elucidate whether gender is an independent risk factor for distribution pattern, we performed multivariable logistic regression models adjusted for cardiovascular risk factors. At time of diagnosis, women with CLI presented with higher mean age (78 ±10 vs 74 ±10, P = .01), suffered more often from hypertension (83% vs 71%, P = .04), and fewer were current or former smokers (25% vs 70%, P < .001). After multivariate analysis, women with CLI showed a 2.5-fold higher risk for femoropopliteal lesions (odds ratio [OR], 2.53; 95% confidence interval [CI], 1.05-6.11, P = .04), with a threefold higher risk for occlusions compared with men (OR, 3.81; 95% CI, 1.45-10.0; P = .01). Moreover, in women a higher risk for multilevel disease was observed (OR, 3.81; 95% CI, 1.45-10.0; P = .01). In contrast, men presented more often with isolated BTK lesions compared with women (OR, 0.15; 95% CI, 0.05-0.70; P = .03). The finding that female gender may be an independent predictor for pronounced femoropopliteal involvement and more severe and diffuse atherosclerotic disease in CLI may be of particular relevance for early detection and for choosing distinct treatment strategies in women compared with men. Further studies are warranted, especially on confounding risk factors that might be different in men and women and their possible association with lesion morphology in patients with critical limb ischemia.